Implementasi Pembiasaan Menabung Untuk Membentuk Sikap Disiplin Anak Usia 4-5 Tahun - Fadhillah, Via Nur; Apriliyanti, Dian Surya; Atikah, Cucu (Innovative: Journal Of Social Science Research, 2025)
The implementation of saving habits to form a disciplined attitude in children aged 4-5 years at TK PUTRA II Serang has been carried out well. Discipline is one of the important elements in the formation of children's character that can be developed through simple activities carried out routinely, such as saving habits. The purpose of this study was to describe how the implementation of saving habits can help form a disciplined attitude in children aged 4-5 years. This study uses a qualitative descriptive approach with data collection methods through observation, interviews, and documentation. The subjects of the study were children aged 4-5 years in group A1 at TK PUTRA II Serang. The findings of the study revealed that 1. The savings strategy implemented at TK PUTRA II Serang is quite good, so that by saving it can form a disciplined attitude in children such as obeying the rules, being responsible, and appreciating every process, 2. The challenges of implementing saving habits to form a disciplined attitude are in children, 3. The solution to the challenges of implementing saving habits to form a disciplined attitude in children aged 4-5 years at TK PUTRA II Serang involves the active role of teachers and parents in providing motivation for children in this saving and discipline habit.